IV Thrombolysis for Acute Ischemic Stroke with Unknown Onset in Patients on Oral Anticoagulation - Macha, Kosmas; Sembill, Jochen; Mühlen, Iris; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Cerebrovascular Diseases, 2024)
Introduction: IV thrombolysis (IVT) is established in the unknown or extended time window based on multimodal imaging. Further, increasing evidence exists regarding IVT in patients on oral anticoagulation including direct oral anticoagulants (DOACs). However, data on IVT in ischemic stroke patients on oral anticoagulation with unknown time of stroke onset are sparse. Methods: This study bases on the longitudinal cohort study Stroke Research Consortium in Northern Bavaria (STAMINA; ClinicalTrials.gov Identifier: NCT04357899). Acute ischemic stroke patients treated with IVT in the unknown or extended time window from January 2015 to December 2019 were included. Patient selection was based on multimodal CT or MRI. Patients on oral anticoagulation (vitamin-K antagonist [VKA] or DOAC within 48 h) were eligible for IVT based on INR measurement (VKA) or plasma levels (DOAC) according to an institutional protocol. Primary outcomes were the incidence of any and symptomatic intracranial hemorrhage. Results: Of 170 ischemic stroke patients treated with IVT in the unknown or extended time window, 151 had no oral anticoagulation at stroke onset and 19 were on oral anticoagulation (6 on VKA and 13 on DOAC). The risk of symptomatic ICH according to ECASS II criteria was similar between the patients with and without oral anticoagulation (1 [5.3%] vs. 4 [2.7%], p = 0.453). After adjustment for confounding factors, pre-medication with oral anticoagulation was not associated with symptomatic ICH (aOR 1.02 [0.09-11.02], p = 0.988). Conclusion: IVT for ischemic stroke with unknown onset appeared safe in selected patients on oral anticoagulation with both DOAC and VKA.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Direct oral anticoagulant; Ischemic stroke; IV thrombolysis; Unknown onset; Vitamin-K antagonist